TEACHING VOCABULARY ON PHRASAL VERBS THROUGH GUESSING STRATEGY TO THE ELEVENTH MIA GRADE STUDENTS OF SMA SANTO PETRUS MEDAN IN THE ACADEMY YEAR OF 2016/2017 - Ginting, Aleixia Sandopa Br; Lumban Raja, Viator; Tarigan, Karisma (Kairos English Language Teaching Journal, 2020)
Vocabulary, as one of the knowledge areas in language, plays a great role for learners in acquiring a language. The vocabulary mastery affects someone’s ability in using the language either in spoken or written form. The objectives of this research are to find out the result and the response of students towards the teaching vocabulary on phrasal verbs to the eleventh MIA grade students of SMA Santo Petrus Medan after having been taught through guessing strategy. This research is a Classroom Action Research which is conducted by applying guessing strategy. After six meetings, it can be seen that there is a significant improvement of students’ vocabulary on phrasal verbs. The result of this research shows that the students’ mean score in pre test is 70,71 with 50% and in post test mean score is 91,28 with 94% of the students got score >75. It shows that there is a significant mean score improvement between pre test and post test about 44%. The responses of students to the teaching vocabulary on phrasal verbs through guessing strategy is good with 56% of agree respond category and 38% of strongly agree respond category. It is suggested that teachers use guessing strategy in teaching vocabulary on phrasal verbs to the students in senior high school to improve their speaking skill.